Effects Of Zno Nanoparticles on Initial Adhesion and fimH Gene Expression Level of Uropathogenic Eschercia coli - Ali Shakerimoghaddam; Ezzat A. Ghaemi; Ailar jamalli (Golestan University Of Medical Sciences, 2017)
Introduction: Uropathogenic Escherichia coli (UPEC) strains are the main causes of urinary tract infections. Adhesion is one of the main and primary steps of UPEC pathogenicity. Type 1 fimbriae is one of the bacterial surface structures that plays an important role in bacterial adhesion. The aim of this study was to evaluate effects of ZnO nanoparticles on the initial adhesion and fimH gene expression level of UPEC. Materials and Method: Four UPEC isolates were used in this study. All isolates were exposed to sub-minimum inhibitory concentration of ZnO nanoparticles (1250 μg/ml). Expression of the fimH gene was evaluated by Real-time PCR. Result: According to the results, presence of nanoparticles reduced the fimH expression level in all four isolates. The highest and lowest rates of down-expression were 1.4-fold and 16.37-fold, respectively. Moreover, these results were consistent with phenotypic observations. Conclusion: However, it is recommended to conduct further studies on gene expression and bacterial adhesion to surfaces to prove whether ZnO nanoparticles could completely prevent UPEC adhesion.